The photographer eaudiobook A novel. - Carter, Mary Dixie (Macmillan Audio, 2021)
This program includes a bonus conversation between Mary Dixie Carter and Jennifer Hillier. Mary Dixie Carter's The Photographer is a slyly observed, suspenseful story of envy and obsession, told in the mesmerizing, irresistible voice of a character who will make you doubt that seeing is ever believing. WHEN PERFECT IMAGES As a photographer, Delta Dawn observes the seemingly perfect lives of New York City's elite: snapping photos of their children's birthday parties, transforming images of stiff hugs and tearstained faces into visions of pure joy, and creating moments these parents long for. ARE MADE OF BEAUTIFUL LIES But when Delta is hired for Natalie Straub's eleventh birthday, she finds herself wishing she wasn't behind the lens but a part of the scene—in the Straub family's gorgeous home and elegant life. THE TRUTH WILL BE EXPOSED That's when Delta puts her plan in place, by babysitting for Natalie; befriending her mother, Amelia; finding chances to listen to her father, Fritz. Soon she's bathing in the master bathtub, drinking their expensive wine, and eyeing the beautifully finished garden apartment in their townhouse. It seems she can never get close enough, until she discovers that photos aren't all she can manipulate. A Macmillan Audio production from Minotaur Books "The sense of impending disaster is palpable, as the suspense and tension grow, and what happens at the end is unexpected and odd. Creepy, dark, and suspenseful...A gripping read." — Booklist